Pengalaman Fisik Dan Psikologis Bidan Desa Puskesmas Cimareme Dalam Menghadapi Pandemi Covid-19 - Ratna Ratna; Ruswana Anwar (Jurnal Kesehatan Rajawali, 2023)
The increase in COVID-19 cases is a major challenge for health facilities and health workers. Previous research has reported that health workers treating COVID-19 patients experience physical and psychological stress. Village midwives during the pandemic received additional duties in handling and monitoring COVID-19 patients in their working areas. This study aims to explore village midwives' physical and psychological experiences in dealing with their duties and responsibilities during the COVID-19 pandemic. This research uses a qualitative phenomenological approach design. Subject selection technique using a homogenous sampling technique. The subjects in this research consisted of key informants, namely the Village Midwife and triangulation informants, namely the Head of the Community Health Center and the Coordinating Midwife. The determination of research subjects and the number of subjects in this research applies the principles of suitability and adequacy. The results of the research show that the village midwives at the Cimareme Health Center experienced the impact of physical and psychological pressure in dealing with their duties and responsibilities during the COVID-19 pandemic. The physical experiences experienced by the Village Midwife at the Cimareme Health Center are fatigue, lack of sleep, disturbed eating patterns, decreased body weight, decreased immune system, illness and contracting COVID-19. The psychological experiences felt by the village midwives at the Cimareme Health Center are worrying about their own and their family's health, fear of contracting COVID-19, worrying about problems that arise, sad to face death cases, depressed to face cases, and pressured to face the community.